IDENTIFIKASI FITOPLANKTON PADA PERUT IKAN SELINCAH (Belontia hasselti) DARI RAWA MENTUKUL DI KABUPATEN BANGKA SELATAN - Pratama, Eko; Bidayani, Endang; Kurniawan, Ardiansyah (Journal of Aquatropica Asia, 2022)
The Selincah fish (Belontia hasselti) is a local Indonesian fish that is widely consumed and has the potential to become ornamental fish. This fish must be domesticated to suppress its exploitation from natural catches. The domestication process requires biological information including eating habits. For this reason, in this study, the identification of phytoplankton contained in the stomach contents of the agile fish was carried out. Fish samples were obtained from Rawa Metukul, South Bangka Regency. The types of phytoplankton in the stomach and intestines of lively fish are the classes Bacillariophyceae, Chlorophyceae, Cyanophyceae, Chlorophyceae, Chrysophyceae, Chrysophyceae. The most dominant species were found in the Chlorophyceae class with an Index of preponderance value of 42.42%, while the Chrystophyceae class was found at least 2.99%.